Surgical management of a second degree perineal laceration in a buffalo sequel to dystocia - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Hashim, Nur Hazirah; Osman, Abdinasir Yusuf; Haron, Abdul Wahid; Yimer, Nurhusein; Awang, Dayang Norhaizam; Roslim, Noorashimah (Pashupati Foundation India, 2014)
A 3-year-old female Murrah-Ravi Buffalo weighing approximately 300 kg suffered a second degree perineal laceration following forced extraction due to dystocia caused by malpresented fetus on 13th October, 2012. Physical examinations modification as a detailed clinical examination that included both physical examination and an obstetrical examination revealed extensive, necrotic and foul smelling vulva with tear which extends from the ventral aspect of the anus to dorsum of the vulva and vagina. In rural or urban conditions fetal traction attempted by farm workers or the owners themselves without veterinary supervision and guidance always lead to complication. Flunixin meglumine (Banamine®) was administered before the wound cleaning and uterine lavage. Epidural anaesthesia was performed before debridement of necrotic tissues and surgical repair of the perineal laceration. The buffalo responded well to the treatments, however handling of dystocia cases under the supervision of veterinary surgeon is imperative even in farms which are aimed at the welfare of inflicted animals in order to avoid serious mishaps' and future breeding of the buffalo is not advisable.